2018
DOI: 10.1021/acscentsci.8b00551
|View full text |Cite
|
Sign up to set email alerts
|

Transferable Machine-Learning Model of the Electron Density

Abstract: The electronic charge density plays a central role in determining the behavior of matter at the atomic scale, but its computational evaluation requires demanding electronic-structure calculations. We introduce an atom-centered, symmetry-adapted framework to machine-learn the valence charge density based on a small number of reference calculations. The model is highly transferable, meaning it can be trained on electronic-structure data of small molecules and used to predict the charge density of larger compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
272
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 252 publications
(277 citation statements)
references
References 74 publications
5
272
0
Order By: Relevance
“…This also calls for the fusion of physics and domain knowledge to ML applications in material science. Learning a tensorial property is also challenging and few attempts have been made to solve this issue . The development of models that can predict tensors with symmetry constraints will likely see great interest.…”
Section: Applicationmentioning
confidence: 99%
“…This also calls for the fusion of physics and domain knowledge to ML applications in material science. Learning a tensorial property is also challenging and few attempts have been made to solve this issue . The development of models that can predict tensors with symmetry constraints will likely see great interest.…”
Section: Applicationmentioning
confidence: 99%
“…where the sum runs over a set of reference environments Z i centered around atoms of the same kind as i, and the weights are computed by a regression procedure that is complicated by the fact that the basis set is not orthogonal [18]. In Fig.…”
Section: B Electronic Charge Densitiesmentioning
confidence: 99%
“…The purpose of a statistical learning model is the prediction of regression targets by means of simple and easily accessible input parameters [1]. In chemistry, physics and materials science, regression targets are usually scalars or tensors, including electronic energies [2][3][4][5], quantummechanical forces [6][7][8], electronic multipoles [9][10][11], response functions [12][13][14][15] and scalar fields like the electron density [16][17][18]. For ground-state properties, the regression input usually consists of all the information connected with the atomic structure at a given point of the Born-Oppenheimer surface, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore important to recognize similarities and differences in the requirements that can be addressed via ML among different applications.In this Perspective, we survey recent uses of ML techniques to solve the Schrödinger equation, including the vibrational Schrödinger equation and the electronic problem: the electronic Schrödinger equation and the related problems of constructing exchange-correlation and kinetic energy functionals for Kohn-Sham (KS-) and orbital-free (OF-) density functional theory (DFT) as well as use of ML for semi-empirical approximations used in density functional based approaches such as DFTB (density functional tight binding) and dispersion-corrected DFT (DFT-D). We only consider the use of ML for the solution of the vibrational and electronic SE or the KS equation or the Hohenberg-Kohn (HK) equation and not methods that aim to avoid such solutions (such as those directly mapping the molecular structure to the spectrum or energy or properties without solving for the density or wavefunction [29][30][31][32][33][34][35][36]); we also do not consider uses of ML for other types of quantum mechanical modelling or other types of differential or integral equations [37][38][39][40][41][42].We do not aim to present a comprehensive review but rather a survey allowing similarities and differences of ML uses in all these applications, as well as promising directions for future research, to transpire. This is not a review of ML methods; the key machine learning techniques that found use in quantum chemistry are well reviewed elsewhere [3-5, 43, 44], their description will not be repeated there; the reader is advised to consult the literature for their introduction, such as [45,46] for neural networks, [47,48] for Gaussian process regression (GPR), [49] for kernel ridge regression (KRR; note the similarity in the form of the function representation between GPR and KRR), [50] for genetic algorithms (GA) and [51] for particle swarm optimization.…”
mentioning
confidence: 99%
“…In this Perspective, we survey recent uses of ML techniques to solve the Schrödinger equation, including the vibrational Schrödinger equation and the electronic problem: the electronic Schrödinger equation and the related problems of constructing exchange-correlation and kinetic energy functionals for Kohn-Sham (KS-) and orbital-free (OF-) density functional theory (DFT) as well as use of ML for semi-empirical approximations used in density functional based approaches such as DFTB (density functional tight binding) and dispersion-corrected DFT (DFT-D). We only consider the use of ML for the solution of the vibrational and electronic SE or the KS equation or the Hohenberg-Kohn (HK) equation and not methods that aim to avoid such solutions (such as those directly mapping the molecular structure to the spectrum or energy or properties without solving for the density or wavefunction [29][30][31][32][33][34][35][36]); we also do not consider uses of ML for other types of quantum mechanical modelling or other types of differential or integral equations [37][38][39][40][41][42].…”
mentioning
confidence: 99%